Pembuatan Cireng dari Kolang kaling di Desa Jatirejo, Gunungpati, Semarang - Susanti, Eka; A, Dhimas; Sulistyarini, Indah; W, Ariani Hesti; Suprijono, Agus (Neolectura, 2024)
Kolang kaling is a plant that is highly sought after during the month of Ramadan before Eid al-Fitr. Jatirejo Village is known as a village that produces processed kolang kaling. Processing in Jatirejo is still traditional so that if it is stored for a long time it will quickly become slimy, to prevent it, replace the damping water. However, to further extend the shelf life so far, only sweets are made by soaking in sugar water. It's just that the use of fro mostly as a mixture of drinks. KWT Makmur is a group of women who are trying to be creative with existing commodities in the Jatirejo area, but for the processing of kolang kaling, there are still many obstacles. PKM is carried out in 3 stages, namely site survey, implementation and evaluation. Cireng is a light snack that is very popular with both children and adults. Cireng so far is only made from starch (tapioca), with the addition of kolang kaling the nutritional content increases. The method of manufacture is easy and the additives are added with healthy compounds. At the time of implementation, there were 3 stages, namely a welcome explanation of the material about the usefulness of kolang kaling, then training on cireng disposal and the last evaluation. The training was attended by 20 members of KWT Makmur, but the enthusiasm of the residents was very good. Based on the results of the evaluation, 100% of the participants were satisfied and clear about the explanation of the speaker and 80% of the residents would immediately sell cireng.